CALCITONIN NEGATIVE MEDULLARY THYROID CARCINOMA - Jandrić-Kočić, Marijana C (Medicinski časopis, 2025)
Medullary thyroid cancer (MTC) is a neuroendocrine neoplasm that arises from parafollicular C cells. Basal and stimulated calcitonin are used in screening, differential diagnosis, assessment of response to treatment and monitoring of MTC. Calcitonin-negative MTC (MTC with normal values of basal and stimulated calcitonin) is extremely rare (49 cases described in the literature). In the absence of appropriate disease predictors, the diagnosis of calcitonin-negative MTC is not easy and is often delayed. A patient with a nodule in the thyroid gland and diskettely elevated calcitonin values is shown. Calcium gluconate stimulation test and carcinoembryonic antigen were normal, and the existence of MTC was ruled out. After a year, the patient notices pain in the lower part of the spinal column. He is referred to rehabilitation treatment, which does not give significant results. Laboratory work-up determines elevated values of parathyroid hormone, scintigraphy shows an enlarged hyperactive lower left parathyroid gland, and thyroidectomy and lower left parathyroidectomy with lymphadenectomy are performed. Pathohistological examination revealed MTC pT1aNxMx. Immunohistochemical analysis was negative for calcitonin and thyroglobulin, positive for chromogranin A and thyroid transcription factor 1 (Thyroid transcription factor-1. Further randomized clinical trials are needed to identify appropriate predictors of calcitonin-negative MTC. Until then, it is necessary to keep in mind the existence of calcitonin-negative MTC that cannot be identified by basal and stimulated calcitonin and carcinoembryonic antigen.